1960
DOI: 10.4141/cjps60-009
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Cereal Grains as Companion Crops in Dryland Forage Crop Establishment

Abstract: The effect of wheat, oats, barley, and spring rye as companion crops on the establishment of a perennial forage crop mixture consisting of crested wheatgrass, brome, and alfalfa under arid conditions compared to no companion crop was studied at Swift Current, Saskatchewan. Cereal companion crops reduced the vigour, stand, and subsequent early forage yields of the grass-alfalfa mixtures, but less so if the cereal crop and the forage crop were seeded separately at right-angles to one another. The method of harve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
14
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 2 publications
5
14
0
Order By: Relevance
“…Grass species and alfalfa cultivar in the mixture also influenced seedling density, but to a lesser degree than environmental conditions. These findings also agree with previous studies (Kilcher and Heinrichs 1960;Waddington and Bittman 1983).…”
Section: Plant Densitysupporting
confidence: 94%
See 2 more Smart Citations
“…Grass species and alfalfa cultivar in the mixture also influenced seedling density, but to a lesser degree than environmental conditions. These findings also agree with previous studies (Kilcher and Heinrichs 1960;Waddington and Bittman 1983).…”
Section: Plant Densitysupporting
confidence: 94%
“…These mixed responses likely reflect edaphic and/or environmental conditions that favoured one companion crop more than another at that siteyear. It is commonly assumed that competition from a companion crop will reduce forage seedling density during the establishment year and that subsequent forage yield is correlated to forage plant density (Kilcher and Heinrichs 1960). For personal use only.…”
Section: Companion Crop Effects On Forage Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…In areas such as the Canadian prairies, there is little time for forage growth after the companion crop is harvested. In these areas, forage yields are normally reduced for at least 1 yr after establishment with a companion crop (Kilcher and Heinrichs 1960;Waddington and Bittman 1983;Moyer 1985;Zaman et al 2003). In some studies, the yield loss effect of companion crops was observed on forage legume stands for up to 4 yr after establishment (Moyer 1989;Moyer et al 1995).…”
Section: Seeding Pure Forage Standsmentioning
confidence: 99%
“…The effect of competition under prairie conditions can be reduced by harvesting companion crops early and by seeding the companion crops in widely spaced rows oriented at right angles to the forage (Kilcher and Heinrichs 1960). Also, it is often recommended that companion crops be seeded at half the normally recommended rate (Smoliak and Bjorge 1981 …”
mentioning
confidence: 99%